Electrochemical hydrogen evolution over MoO3 nanowires produced by microwave-assisted hydrothermal reaction - Phuruangrat A. (2014)
Molybdenum trioxide (MoO3) nanowire with unprecedentedly high aspect ratios (>200) and good crystallinity was prepared via decomposition of (NH4)6Mo7O24·4H2O under a microwave-assisted hydrothermal (MH) process. The nanowire was orthorhombic MoO3 with 50 nm in diameter and 10-12 μm in length. The conventional hydrothermal (CH) reaction required higher temperature and longer reaction times to produce one-dimensional MoO3, yet its quality was lower. In the electrochemical hydrogen evolution reaction in a H2SO4 solution, MoO3 nanowire from MH process showed much higher electrocatalytic activity than MoO3 prepared from CH method and commercial bulk MoO3 particles. The facile vectorial electron transport along the nanowire axis was considered to be responsible for the excellent electrocatalytic activity of the MH-MoO3 nanowire. © 2009 Elsevier B.V. All rights reserved.